Avaliação fenotípica e genotípica de segregantes de uma linhagem industrial de Saccharomyces cerevisiae - Ibelli, Flávia Danieli [UNESP] (2014)
Fuel-ethanol fermentation process includes a reutilization of the yeast biomass, in which yeast cells are exposed tostress conditions as high temperature, increasing alcohol concentration and low pH values. This enviroment may cause a significant delay in fermentation and drop in cell viability. Some Saccharomyces cerevisiaestrains, however, have thermotolerance or resistance to higher ethanol concentrations, while being able to adapt to the environment in which they are. In this work, the industrial resistant yeast strain was isolated from fermented sugar cane at the end of the harvest to be good leavening. Aiming to study genetic features associated with cell resistance to sustained stress in an industrial yeast strain, they wereinduced to sporulation and the ascospores were dissected in order to generate homozygous derivatives andwere ramdomly selected for further phenotype analysis. The results have shown that two of segregating presented to be promising with the fermentative capacity and resistance to high temperature and ethanol concentration as compared to industrial strains PE-2, CAT-1 and SA-1. Following that,the real time PCR assay was performed to assess the relationship of APJ1, FPS1, MKT1, SWS2 and HSP12 genes with ethanol tolerance. Furthermore, was also analyzed the differential expression of the HSP12 gene as a molecular marker for stress-resistance in industrial yeast.The PCR was performed with two yeast strains: a resistant yeast (MA-12) and non-resistant (MA-139, ruled in the early experiments) and shows wich all genes evaluated revealed a significant expression in stress situations for the resistantstrain MA-12, which did not happen in the sensitive yeast (except for APJ1 gene), which shows that the selected genes are directly related to stress resistance. The results also suggest that HSP12 gene can be used as a molecular marker of stress in industrial yeast strains, since they have shown significant expression in the ...